An Investigation of Three types of Tooth Implant Supported Fixed Prosthesis Designs with 3D Finite Element Analysis. - Sara Koosha; Fatemeh Sadat Mirhashemi (Tehran University of Medical Sciences, 2013)
Tooth/implant supported fixed prostheses may present biomechanical design problems, as the implant is rigidly anchored within the alveolus, whereas the tooth is attached by the periodontal ligament to the bone allowing movement. Many clinicians prefer tooth/implant supported fixed prosthesis designs with rigid connectors. However, there are some doubts about the effect of attachment placement in different prosthesis designs. The purpose of this study was to examine the stresses accumulated around the implant and natural teeth under occlusal forces using three dimensional finite element analysis (3D FEA).In this study, different connection designs of tooth/implant fixed prosthesis in distal extension situations were investigated by 3D FEA. Three models with various connection designs were studied; in the first model an implant rigidly connected to an abutment, in the second and third models an implant connected to abutment tooth with nonrigid connector in the distal part of the tooth and mesial part of the implant. In each model, a screw type implant (5×11mm) and a mandibular second premolar were used. The stress values of these models loaded with vertical forces (250N) were analyzed.There was no difference in stress distribution around the bone support of the implant. Maximum stress values were observed at the crestal bone of the implant. In all models, tooth movement was higher than implant movement.There is no difference in using a rigid connector, non rigid connector in the distal surface of the tooth or in the mesial surface of an implant.